Place An Introduction - Cresswell, Tim (Wiley, 2014)
Thoroughly revised and updated, this text introduces students of human geography and allied disciplines to the fundamental concept of place, combining discussion about everyday uses of the term with the complex theoretical debates that have grown up around it.  A thoroughly revised and updated edition of this highly successful short introduction to place  Features a new chapter on the use of place in non-geographical arenas, such as in ecological theory, art theory and practice, philosophy, and social theory  Combines discussion about everyday uses of the term 'place' with the more complex theoretical debates that have grown up around it  Uses familiar stories drawn from the news, popular culture, and everyday life as a way to explain abstract ideas and debates  Traces the development of the concept from the 1950s through its subsequent appropriation by cultural geographers, and the linking of place to politics